we can immediately take out an x^8 and a y^1
x^8 y ( x^2 y^2 - 4 x y - 21 )
21 = 3 * 7
3 - 7 = -4
x^8 y ( x y - 7 ) ( x y + 3 )
Thanks a lot, this really helps!
Start by removing the common factor x^8 y.
x^10y^3 – 4x^9y^2 – 21x^8y
= x^8*y(x^2 y^2 -4 xy -21)
The term in parentheses is a quadratic in the variable xy, and can be factored to
(xy -7)(xy + 3).
Now put it all together
Algebra - Ok I got two I need help with : 1. Factor Completely 7x^2 + 49x + 42 I...
ALGEBRA - with multiplying this: 9y^2-9)(8y^2-9y+3) I have: 8y^2(y^2-9)-9y(y^2-9...
Algebra 1 - Factor completely 4x^3+x^2y-36x-9y
Algebra 2 - "My husband's age," remarked a lady the other day, "is represented ...
algebra 2 - I am trying to factor the expression -8y^2+28y-60 but can't get an ...
Algebra 1 - Are these right? xy - 3x - 8y + 24 (3x-y)-(8y+24) 8y+24 4x^2 + 20x...
algebra 1 - I'm stuck on this problem. Can you help? -4x-9y=1 -x + 2y =-4 WHat ...
Algebra 2 - maximize p=6x+10y minimize p=14x+9y use elimination to solve: 4x+5y=...
algebra 1 - completely factor: 10y^2 -90
algebra - factor completely x^2+6xy+8y^2